Fostering Critical Thinking in Academic Writing through a Meta-Reflective Model: Integrating Self-Assessment and Inquiry-Based Learning - Harsono, Harsono; Amalia, Laili; Sanulita, Henny; Aticqa, Emas Malika Balqies Putri; Rahmatullah, Affan Maulidi (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2026)
Academic writing in higher education requires students to demonstrate critical and reflective thinking skills. However, writing instruction rarely provides a systematic model that integrates metacognitive reflection into the writing process. This gap causes students to experience difficulties in linking self-reflection with the development of academic argumentation. This study aims to develop and examine the effectiveness of a meta-reflective writing model that integrates self-assessment and inquiry-based learning to enhance students’ critical thinking skills. The study employed a research and development (R&D) approach encompassing a preliminary study, model design, expert validation, limited trials, and effectiveness testing. The participants consisted of two expert validators and 20 students enrolled in a language education program. Validation results indicated that the model was highly feasible, with a mean score of 4.47. Findings from the limited trials demonstrated improvements in the quality of students’ written argumentation. Effectiveness testing using a one-group pretest–posttest design revealed a statistically significant increase in critical thinking scores from 22.1 to 44.4 (p < 0.001).These findings confirm that the meta-reflective writing model is effective, practical, and relevant as a pedagogical approach for strengthening critical thinking in academic writing, although further refinement of indicators at the pre-writing stage is still required.